A practical numerical model for thin-walled steel connections and built-up members. (April 2022) - Ye, Jun; Quan, Guan; Kyvelou, Pinelopi; Teh, Lip; Gardner, Leroy
Abstract: The interaction between the cold-formed steel members and fasteners in a structural assembly often involves complex stress states, material plasticity, significant in-plane deformations and curling, rendering computational modelling of the resulting structural system challenging. In addition, the presence of initial geometric imperfections and the susceptibility of cold-formed steel members to local instabilities adds a further degree of complexity to the numerical modelling. The behaviour of bolted connections between cold-formed steel members has traditionally been assessed based on physical tests, though these can be time consuming and expensive. In this paper, a practical numerical approach to the simulation of bolted cold-formed steel connections, capturing all the key behavioural features including bolt preload, slippage and bearing, is introduced. Starting from a typical shell finite element (FE) model of a cold-formed steel plate, a small number of solid elements is introduced around the bolt holes, to allow accurate replication of the bolt-ply interaction, with contact pairs defined between the bolts and the surrounding material. An explicit dynamic solver is then employed to solve the geometrically and materially nonlinear problem, both with and without bolt slippage. Validation of the FE model is conducted using benchmark tests reported in the literature. It is shown that the proposed numerical method can accurately capture the structural behaviour of bolted cold-formed steel connections and cold-formed steel built-up sections, while being computationally efficient and numerically stable; the proposed approach is therefore recommended for the numerical modelling of cold-formed steel systems assembled using fasteners.